Driving factors for rice farmers productivity in Abia State, Nigeria - Raymond, Ndunewe Chiedozie (2024)
Crop production management is a critical global issue, particularly in developing countries like Nigeria where agriculture is the largest contributor to food, employment opportunities and foreign earning. While total rice productivity in Nigeria has increased over the years, rice farmers have struggled to meet the demand since 2016, as consumption has outpaced production, leading to a rise in rice imports. Several factors contributed to this productivity challenge. Therefore, this study aims to examine the relationship between access to credit, new technology, government policy, and climate change as factors influencing the productivity of rice farmers. This study employs a quantitative research design, and it focuses on rice farmers in Abia State. Data were collected from 379 respondents through a structured questionnaire distributed via email using a simple random sampling technique. Hypotheses were analyzed using correlation coefficients with the Statistical Package for Social Sciences (SPSS). The findings indicate a positive but non-significant relationship between credit availability and rice productivity. Additionally, there is insignificant correlation between new technology and rice productivity. Furthermore, there is a positive but insignificant relationship between government policy and rice productivity. However, a negative relationship exists between climate change and rice productivity. The government may use the results of this study as a basis for implementing effective policies aimed at increasing the productivity of rice farmers and also understand more on easy credit accessibility options from financial institutions. Additionally, the demographic perspectives gained from this study will assist future researchers in understanding the credit options available to rice farmers and their productivity levels.